Pengaruh STEAM-PjBL pada Pembelajaran Matematika terhadap Kepercayaan Diri Siswa SD - Subekti Wining Anggraini; Herwin Herwin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
STEAM-PjBL is a learning model that theoretically has the potential to influence elementary school students' self-confidence in learning Mathematics. In addition, low self-confidence is a problem that is often found in schools. This study aims to test the effect of the STEAM-PjBL learning model in mathematics learning on elementary school students' self-confidence.The study was conducted using a quasi-experimental design. The subjects in the study were 35 sixth grade students of SDN Karangrejek I, Kapanewon Wonosari in the 2024/2025 academic year. The sampling technique was simple random sampling. Data collection techniques used observation and questionnaires. Data analysis was carried out using descriptive and inferential analysis techniques. The results of the study showed that the hypothesis test of students' self-confidence using the independent sample t-test obtained a significance value (2-tailed) equal variances assumed 0.006 <0.05 so that it can be concluded that there is an influence of the STEAM-PjBL learning model in mathematics learning on the self-confidence of elementary school students.